2018
DOI: 10.1115/1.4039496
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Optimal Hopping in Parallel and Series Elastic One-Dimensional Monopeds

Abstract: In this paper, we examine the question of whether parallel elastic actuation or series elastic actuation is better suited for hopping robots. To this end, we compare and contrast the two actuation concepts in energy optimal hopping motions. To enable a fair comparison, we employ optimal control to identify motion trajectories, actuator inputs, and system parameters that are optimally suited for each actuator concept. In other words, we compare the best possible hopper with parallel elastic actuation to the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…As animal structure and motion have simultaneously evolved to be specifically designed to perform desired tasks efficiently and effectively, it is essential to account for both morphology and motion in robot design and control. Yesilevskiy et al (2015Yesilevskiy et al ( , 2018a discussed the effect of morphological variations in legged robots, and showed for a one-dimensional monoped hopper that is driven by a geared DC motor, with the correct choice of the transmission parameter, a hopper with Series Elastic Actuators (SEA) is more energetically efficient than one with Parallel Elastic Actuator (PEA). It is mostly due to the fact that, for a hopper with PEA, the motor inertia contributes to energetic losses due to the ground contact collisions.…”
Section: Compliant Actuationmentioning
confidence: 99%
“…As animal structure and motion have simultaneously evolved to be specifically designed to perform desired tasks efficiently and effectively, it is essential to account for both morphology and motion in robot design and control. Yesilevskiy et al (2015Yesilevskiy et al ( , 2018a discussed the effect of morphological variations in legged robots, and showed for a one-dimensional monoped hopper that is driven by a geared DC motor, with the correct choice of the transmission parameter, a hopper with Series Elastic Actuators (SEA) is more energetically efficient than one with Parallel Elastic Actuator (PEA). It is mostly due to the fact that, for a hopper with PEA, the motor inertia contributes to energetic losses due to the ground contact collisions.…”
Section: Compliant Actuationmentioning
confidence: 99%
“…The key aspect making this problem one of co-design is the additional decision variables in ρ, which contains the design parameters: motor masses, spring stiffnesses and gear ratios. The motor constant and inertia of each motor were related to the motor mass by the relationships presented in [15] and reported in the technical report [20]. Detailed path and boundary constraints (12c) and (12d) are provided in [20] as well.…”
Section: -Dof: Modelmentioning
confidence: 99%
“…The frequency range in the analysis goes from 0.1 to 10 Hz, with 0.1 Hz resolution. The set of values for the spring stiffness is [30, 50, 100] Nm/rad, while for the gear ratio of the SEA it is [5,10,15,20,30,50,100,150,200].…”
Section: A 1-dof: Test Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint parallel compliance can be viewed from the standpoint of biologically inspired design, mimicking the compliant property within muscles and ligaments, as well as joint capsules. Theoretical studies have revealed that the addition of physical parallel compliance is beneficial to reduce peaks of motor torque and power, and even energetic cost, provided that the parallel compliant mechanism is designed and tuned properly [56][57][58][59][60][61].…”
Section: Category Ii: Joint Parallel Compliancementioning
confidence: 99%